Analisis Iklan Instant Messaging Terhadap Promosi Tumblr Day Pada Official Account Line Starbucks Indonesia Perspektif Islam - Novy Putri; Siti Sundari; Sundari Sundari (Jurnal Ilmiah Ekonomi Islam, 2022)
Along with the development of the digital era, there is a lot of information about several things that we can easily get. Starting from health, food, drinks, sports, to the style of dress. Likewise with the world of marketing they also play a role in it to do promotions. This article aims to analyze the advertisements carried out by Starbucks for the Tumbler Day promotion given every Thursday. The libratu research method is used to strengthen the fact to see Instant ads on Starbucks Line accounts, are they in accordance with the Islamic perspective that the researchers are researching? This study shows that digital marketing carried out by Starbucks Corporation contains fraud because the information provided is not in accordance with its application when we arrive at Starbucks outlets. The 50% discount only applies to payments using a Starbucks card, if you pay using another payment method, a 30% discount is only applicable. This is where the principles of honesty and fairness are not met by the Starbucks corporation.